2020
DOI: 10.1152/ajpgi.00349.2019
|View full text |Cite
|
Sign up to set email alerts
|

Fermentable fibers induce rapid macro- and micronutrient depletion in Toll-like receptor 5-deficient mice

Abstract: Feeding a dietary, fermentable fiber diet to a subset of Toll-like receptor 5 deficient (T5KO) mice induces early onset hyperbilirubinemia and cholemia that later manifests to hepatocellular carcinoma (HCC). Our study highlights that fermentable fiber-induced cholestasis is characterized with modest macro- and micronutrient deficiencies that may further contribute to hepatic biliary disease. Compared with chemical induction, immunization, surgery, or genetic manipulation, these findings provide a novel approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Furthermore, our model utilized Toll-like receptor 5 deficient (T5KO) mice that have a compromised innate immune system, which we have previously described increased their susceptibility to metabolic syndrome [56]. Despite these potential drawbacks, we believe that robust fermentable fiber-induced HCC offers as a promising model for the following reasons: (i) presents a novel approach to study metabolic function to tumor formation, analogous to HCC susceptibility found in Acox-deficient mice that have impaired fatty acyl-CoA oxidase and βoxidation [57], (ii) serves as an alternative model to study cholestatic HCC compared to previous mouse models with genetic ablation of either ABCB4 or MDR2 [58], (iii) allows to mechanistically understand the role of the gut microbiota in HCC, which is becoming well recognized as a strong influencer through the gut-liver axis [59], and (iv) this model recapitulates known consequences of cholestasis that is exhibited in humans such as depletion of essential fatty acids and fat-soluble vitamins [60]. Notwithstanding, HCC incidence has been continuing to increase for the past couple of decades, and while this is reported to be largely due to viral infection, refined fermentable fibers may be another unknown risk factor.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, our model utilized Toll-like receptor 5 deficient (T5KO) mice that have a compromised innate immune system, which we have previously described increased their susceptibility to metabolic syndrome [56]. Despite these potential drawbacks, we believe that robust fermentable fiber-induced HCC offers as a promising model for the following reasons: (i) presents a novel approach to study metabolic function to tumor formation, analogous to HCC susceptibility found in Acox-deficient mice that have impaired fatty acyl-CoA oxidase and βoxidation [57], (ii) serves as an alternative model to study cholestatic HCC compared to previous mouse models with genetic ablation of either ABCB4 or MDR2 [58], (iii) allows to mechanistically understand the role of the gut microbiota in HCC, which is becoming well recognized as a strong influencer through the gut-liver axis [59], and (iv) this model recapitulates known consequences of cholestasis that is exhibited in humans such as depletion of essential fatty acids and fat-soluble vitamins [60]. Notwithstanding, HCC incidence has been continuing to increase for the past couple of decades, and while this is reported to be largely due to viral infection, refined fermentable fibers may be another unknown risk factor.…”
Section: Plos Onementioning
confidence: 99%
“…Despite being an anomaly, murine PSS is nonetheless an invaluable animal model with clinical relevance to humans with patent ductus venosus , 33 those who acquire spontaneous PSS due to liver cirrhosis, 39 and those who had underwent surgery for transjugular intrahepatic portosystemic shunt (TIPS; a surgically created shunt) to reduce portal hypertension. 40 In many aspects, PSS mice recapitulate phenotypes of their human counterparts, 33 including the propensity for hyperammonemia, 1 macro and micronutrient deficiencies, 41 and metabolic perturbations. 2 , 9 , 10 Hence, we posit that PSS mice could be further developed as the sought-after preclinical model to study novel treatments for a spectrum of PSS-related complications such as neonatal cholestasis and hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%